Geothermal energy challenge : Guardbridge geothermal technology demonstrator project /: Guardbridge geothermal technology demonstrator project. (2016) - Rambøll (Firm),; Town Rock Energy,; University of St. Andrews,; Resource Efficient Solutions LLP,; British Geological Survey,
No abstract available